2020
DOI: 10.1158/1557-3265.covid-19-po-009
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PO-009: Cancer-related distress among multiple myeloma patients during the COVID-19 pandemic

Abstract: Background: The rapid outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the delay of non-urgent or routine medical appointments, placing tremendous burden on cancer patients. Meanwhile, the emotional effect of the novel coronavirus (COVID-19) on high-risk groups, such as multiple myeloma (MM) patients, remains unclear. The purpose of this project was to understand psychosocial distress and unmet needs among patients with active MM during the acute phase of social distancing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…COVID-19 greatly affects not only the physical health, but also the psychological health of people (Ornell et al, 2020 ; Sweeney and Ahlstrom, 2020 ; Sun and Li, 2021 ; Wong et al, 2021 ). Fear and anxiety are the psychological response of many people to COVID-19 pandemic, including cancer patients, and these people experience a significant psychological burden at the current time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 greatly affects not only the physical health, but also the psychological health of people (Ornell et al, 2020 ; Sweeney and Ahlstrom, 2020 ; Sun and Li, 2021 ; Wong et al, 2021 ). Fear and anxiety are the psychological response of many people to COVID-19 pandemic, including cancer patients, and these people experience a significant psychological burden at the current time.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a retrospective study of 160 patients with or suspected of breast cancer showed that COVID-19 related anxiety could discourage treatment (Vanni et al, 2020 ). A survey of 1,079 patients with multiple myeloma showed that they have concern about the future and events ahead, worries about family, friends and relatives, and also have paternal irritation, feelings of sadness, anger, fear, loneliness, and problems communicating with their spouses during the COVID-19 pandemic (Sweeney and Ahlstrom, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The concerns raised by the participants of the study require the university to provide access to considerable support to deal with the struggles, challenges, and even trauma because of the pandemic. There is a need to help manage mental health, selfesteem, and relationships after the quarantine which left some of the students isolated for quite a time (Sweeney, 2020). Mental health programs have to be in place in formal learning settings.…”
Section: Theme 4 Maslow Before Bloom Orientation: Safety and Securitymentioning
confidence: 99%
“…22 Therefore, HealthTree Cure Hub practices a patient-input and medical consultant-verified approach to maximize the potential for population-based analyses and to draw reliable conclusions. As a result, we have published nine abstracts, seven to ASCO [23][24][25][26][27][28][29] and two to the American Association of Cancer Research, 30,31 and published one peer-reviewed manuscript in Dermatologic Therapy, 18 with others in preparation.…”
Section: Discussionmentioning
confidence: 99%